Cenobamate reduces epileptiform activity in the ex vivo F98 rat glioma model - Forberger, Ferdinand; Santana Kragelund, Fabiana; Porath, Katrin; Köhling, Rüdiger; Kirschstein, Timo; Lange, Falko (Frontiers in Neuroscience, 2025)
IntroductionEpileptic seizures are a common clinical sign in patients suffering from high-grade glioma. In addition to therapeutic interventions aiming to prolong the remaining lifespan, maintaining quality of life is a cornerstone of current treatment concepts. Consequently, anticonvulsants are frequently applied to keep seizures at bay, but drug resistance is still a challenge. There is a need for new anticonvulsants to address this issue. Therefore, for the first time, we evaluated the efficacy of cenobamate, a novel anticonvulsant shown to inhibit persistent sodium currents and modulate GABAA receptor function, in a preclinical model of glioma-associated epilepsy. In our study, we used cortical slices from naive Fischer rats and animals with orthotopically implanted F98 tumors.MethodsTo study the effect of cenobamate (60 and 120 μmol/L), we recorded local field potentials and evoked spontaneous network deflections using an acute disinhibition solution. To analyze seizure-like events (SLEs), we employed a deep learning approach, further supported by power spectral density (PSD) analysis.ResultsCenobamate attenuated the proportion of recording time occupied by SLEs, mainly by reducing their duration in slices of both sham-operated and F98 tumor-bearing animals. Additionally, the spike load within SLEs was diminished by the anticonvulsant. The PSD analysis confirmed the reduction of spike frequencies abundant in seizure-like events.ConclusionOur data show that cenobamate effectively reduced the epileptic phenotype in glioma-bearing brain slices. We hence suggest that cenobamate may effectively contribute to seizure control in tumor-associated epilepsy.